DIAGNOSIS AND SURGICAL TREATMENT OF ACUTE DESTRUCTIVE CHOLECYSTITIS IN REGIONAL HOSPITALS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Cholecystectomy is a radical intervention leading to a complete recovery of the patient. Materials and methods. The study material was the medical records of 77 patients operated on in the Khankinsky district hospital in 2023 for acute cholecystitis within 72 hours of the onset of the disease. Results. A clinical examination revealed acute destructive cholecystitis in 35 out of 42 people, and acute cholecystitis in 26 out of 35 patients. Conclusion. Thus, in order to timely resolve the issue of urgent laparoscopic cholecystectomy in a regional hospital, the diagnosis of acute destructive cholecystitis with a high degree of reliability can be established by identifying a combination of clinical, ultrasound signs and changes in functional liver tests.